Hubungan body condition score (BCS) dan bobot badan dengan produksi susu sapi perah PFH di unit KPSP setia kawan nongkojajar pasuruan - Noor Iqomathus Sya'adah; Puguh Surjowardojo (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2022)
The purpose of this research was to determine the relationship between BCS and body weight to milk production of Friesian Holstein crossbreed dairy cattle. The material used for this research were 45 dairy cattles that lactating period in 3,4, and 5. The study was conducted in KPSP setia kawan nongkojajar pasuruan on 28 August-30 October 2021. The method used in this research is direct survey to the farm. The data collection technique in this study was purposive sampling. The variables observed in this study were BCS, boby weight, and milk production. Data obtained were analyzed by used correlation analysis, and simple linear regression analysis. The linier regression equation between BCS and milk production shows Y= 12.178+2.899X with a correlation coefficient is 0.309 and for the coefficient of determination is 9.5%. The linier regression equation between body weight and milk production shows Y= -0.635+0.044X with a correlation coefficient is 0.488 and the coefficient of determination is 23.8%. The result of research indicate that there was a significant relationship between BCS and body weight to milk production.